McTaggart's series and the ancient philosophy of time - Golitsis, Pantelis (Neusis, 2024)
McTaggart’s thesis about the unreality of time still puzzles philosophers of the metaphysics of time, who defend the existence either of the A series or the B series. McTaggart himself, however, was led through his analysis to view as real what he called ‘the C series’, which, unlike the temporal A and B series, is atemporal. I argue that the ancient conceptions of time, especially of Aristotle and Damascius, overcome McTaggart’s claim about the unreality of time by explaining, retrospectively, how the B series is generated from the C series without the involvement of the A series, which has been shown by McTaggart to have a contradictory nature. This comparison enables us to see not only that Damascius was the first presentist in the history of the metaphysics of time, but also that McTaggart’s analysis rests upon the unreflected assumption that time progresses linearly.